Properties of Low Activity Clay Soils from South Kalimantan - BAMBANG HENDRO PRASETYO; NATA SUHARTA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2004)
Soils with low activity clay is one of the problem soils in Indonesia. These soils consisted of Ultisols, Oxisols, Alfisols, and some Inceptisols, occupied about 34.5% of total Indonesian land, distributed in almost all Indonesian islands, and derived from various parent materials. To evaluate the properties of low activity clay soils, 6 pedons of Oxisols and Inceptisols, derived from clay stone, andesitic rock, ultra mafic rock and lime stone,from South Kalimantan were studied both in the field and in the laboratory. The analyses consisted of texture, organic carbon content, pH (H2O and KCl), potential P and K, available P, P retention, exchangeable bases and acidity, cation exchange capacity and mineralogical composition. The results showed that low activity clay dominated by opaque and quartz as primarilyresistant mineral. Clay fraction was dominated by kaolinite, and to a lesser extent goethite, hematite, and gibbsite were also present. The mineralogical composition of the low activity soils indicated a low natural potential nutrient reserve and an advanced stage of soil weathering. Chemically, the low activity clay soils were acid, low content of bases, low cation exchange capacity, high P retention, and some of them show a high aluminum saturation. A complete fertilizer application is necessary for a sustainable use. Although soil fertility constraints on the low activity clay soils can be corrected by liming and appropriate fertilization, socioeconomic condition of the local farmer is another constraint.